A vida na fazenda : sentidos subjetivos do servidor fazendário frente à participação no trabalho - Silveira, Rogério Zanon da (2010)
This study deals with the theme of participation at work when it comes to Public Administration. The participation concept adopted is associated to the forms and the means by which workers and leaders of an organization can influence their destinies (MOTT